(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2023)
информация. Информационная безопасность является глобальной проблемой в связи с опасной зависимостью общества от глобальной сети Интернет, а киберугрозы сети одной из самых серьезных проблем экономики и национальной безопасности. Информационная безопасность стала избирательным избирательным приоритетом. Всем организациям, включающим образовательные учреждения, работающим с использованием цифровых компьютерных технологий, требующих специалистов, обладающих компетенциями и навыками, включающими познавательные, управленческие и технические знания для борьбы с кибератаками в динамичной среде киберугроз.В связи с этим растет спрос не только на квалифицированных специалистов, но и на преподавателей, обладающих компетенциями в области информационной безопасности, способных обучать основам кибербезопасности со школьной скамьи. The existing contradictions between the widespread use of digital technologies that are vulnerable to cyber attacks, and the lack of use of the educational process for teaching information security, as well as between the increasing demand for training computer science teachers in information security and the lack of readiness of the university’s teaching staff to train relevant specialists, allow us to formulate an urgent problem of scientific research. The problem lies in the need for systematic training of future teachers of computer science and the formation of their professional competencies in information security in the modern conditions of the development of the information society. The novelty of the research is the development of an approach to teaching future computer science teachers the basics of cybersecurity and the formation of their competencies in information security in the context of digitalization of education.